Simple synthesis and characterization of vertically aligned Ba0.7Sr0.3TiO3–CoFe2O4 multiferroic nanocomposites from CoFe2 nanopillar arrays. (31st October 2017) - Basov, Sergey; Elissalde, Catherine; Simon, Quentin; Maglione, Mario; Castro-Chavarria, Christopher; de Beauvoir, Thomas Herrison; Payan, Sandrine; Temst, Kristiaan; Lazenka, Vera; Andrei Antohe, Vlad; de Sá, Pedro Miguel Pereira; Sallagoity, David; et al.
Abstract: A new strategy to elaborate (1-3) type multiferroic nanocomposites with controlled dimensions and vertical alignment is presented. The process involves a supported nanoporous alumina layer as a template for growth of free-standing and vertically aligned CoFe2 nanopillars using a room temperature pulsed electrodeposition process. Ba0.70 Sr0.30 TiO3 –CoFe2 O4 multiferroic nanocomposites were grown through direct deposition of Ba0.7 Sr0.3 TiO3 films by radio-frequency sputtering on the top surface of the pillar structure, with in situ simultaneous oxidation of CoFe2 nanopillars. The vertically aligned multiferroic nanocomposites were characterized using various techniques for their structural and physical properties. The large interfacial area between the ferrimagnetic and ferroelectric phases leads to a magnetoelectric voltage coefficient as large as ∼320 mV cm −1 Oe −1 at room temperature, reaching the highest values reported so far for vertically architectured nanocomposite systems. This simple method has great potential for large-scale synthesis of many other hybrid vertically aligned multiferroic heterostructures.